A hybrid algorithm for studying the effects of various uncertainties on the nonlinear dynamic responses of steel storage tanks subjected to seismic base excitation. (November 2022) - Khayat, Majid; Baghlani, Abdolhossein; Dehghan, Seyed Mehdi
Abstract: Uncertainty in the basic load and strength variables of a steel storage tank can significantly affect its structural performance and safety. Additionally, due to the inherent uncertainties affecting the various sources in practical situations, their handling in the nonlinear modeling methodology has nowadays become essential. However, it is still an issue to be investigated. Thus, this paper presents a numerical modeling methodology intended to determine the effects of various uncertainties on the dynamic responses of the liquid-shell systems of aboveground steel storage tanks under seismic base excitations. The uncertainties include mechanical properties of materials, geometry properties, liquid properties, and excitation parameters. The uncertain dynamic response of large steel aboveground storage tanks is investigated by using a hybrid algorithm. Eight tall liquid storage tanks with aspect ratios greater than unity are considered. The considered tanks have a similar radius but different heights. The effects of aspect ratio and liquid level on nonlinear dynamic responses are discussed. The point estimation method and the artificial neural network-based algorithm were used to simulate the sources of uncertainty and extract the statistical properties, including the probability density functions (PDF), and the cumulative distribution functions (CDF). An efficient approach with low computational cost compared to the conventional finite element method is proposed based on a combination of the boundary element method and the semi-analytical finite strip to analyze the flexible steel storage tanks subjected to seismic base excitation. Concentric annular rings are used to model the free surface of the liquid. The nonlinearities corresponding to both material properties and geometry deformations are included. According to uncertainty sources, a sensitivity analysis is also carried out. The results show that lognormal probability distribution is more suitable for predicting nonlinear dynamic responses of steel storage tanks under seismic base excitations.